Efektivitas Cendawan Cordyceps militaris pada Berbagai Media terhadap Hama Ulat Api (Setothosea assigna L.) - Ginting, Jordanta; Kuswardani, Retna Astuti; Pradana, Mahardika Gama (Jurnal Ilmiah Pertanian ( JIPERTA), 2026)
This research aims to determine the growth response of Cordyceps militaris in several growing media, determine the best growing media for cultivating Cordyceps militaris and determine the effectiveness of cultivating Cordyceps militaris against fire caterpillar larvae (Setothosea assigna). This research was carried out using a non-factorial Completely Randomized Design method, with 3 growing media treatments, namely N1 = Bran, N2 = Rice and N3 = Corn. The number of repetition was 6. Data analysis uses Anova, where if the results showed a significant and very siognificant effect, it was continued with Duncan’s Multiple Range Test (DMRT). The results showed that the growth medium had no significant effect on the density of yellow fungus and white fungus conidia, the viability of yellow fungus and white fungus condidia. The growth media of C. militaris is found in brand media, which is observed from the viability of fungus, both in yellow and white conidia, which can kill Setothosea assigna larvae which are marked in bran, rice and corn media at the age of 11-19 day after application, causing mortality between 93,34-100%,